Pengembangan Literasi dalam Buku Teks Panggelar Basa Sunda Untuk SMA/SMK/MAK Kelas XI (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2022)
This research was motivated by the discovery of literacy development contained in Sundanese language textbooks at the SMA/SMK/MA/MAK equivalent level. This literacy development is important to be studied further, so that it can be used as a model in the application of literacy development to students. Based on this background, this study aims to describe the development of literacy contained in the Panggelar Basa Sunda text book for students of SMA/SMK/MA/MAK class XI. The method used in this research is descriptive qualitative by using literature study technique. The research data source is a Sundanese language textbook entitled Panggelar Basa Sunda pikeun SMA/SMK/MA/MAK students class XI 2013 revised 2017 curriculum, while the research data are 8 KD or 8 chapters contained in the contents of the textbook. After being analyzed, the textbook has criteria that are very feasible and easy to understand. The development of highly qualified literacy is able to support more competent, creative, productive resources and have high fighting values ​​in facing the era of globalization.